2018
DOI: 10.1021/acscatal.8b02232
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of a Single-Site Gold-on-Carbon Acetylene Hydrochlorination Catalyst: An X-ray Absorption and Inelastic Neutron Scattering Study

Abstract: Single-site Au species supported on carbon have been shown to be the active sites for acetylene hydrochlorination. The evolution of these single-site species has been monitored by Au L 3 X-ray absorption spectroscopy (XAS). Alternating between a standard reaction mixture of HCl/C 2 H 2 and the single reactants has provided insights into the reaction mechanism and catalyst deactivation processes. We demonstrate that oxidative addition of HCl across an Au(I) chloride species requires concerted addition with C 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 43 publications
2
59
1
Order By: Relevance
“…In the fresh Au/AC catalyst, the relative content of Au 3+ and Au 0 were 55 % and 45 %. The Au 0 existed in fresh Au/AC might be originated from the reduction of Au 3+ to Au 0 by the carboxyl functional groups on the carbon surface ,,. Besides, carbon with low reduction potential is also capable of reducing Au 3+ to Au 0 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fresh Au/AC catalyst, the relative content of Au 3+ and Au 0 were 55 % and 45 %. The Au 0 existed in fresh Au/AC might be originated from the reduction of Au 3+ to Au 0 by the carboxyl functional groups on the carbon surface ,,. Besides, carbon with low reduction potential is also capable of reducing Au 3+ to Au 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, nonmercuric catalytic systems are urgently required in consideration of safety and green chemistry. To resolve this problem, a series of metal chlorides catalytic systems employing AuCl 3 , PdCl 2 ,, RuCl 3 and CuCl 2 as catalysts have been investigated by Hutchings et al . and many other research groups for acetylene hydrochlorination.…”
Section: Introductionmentioning
confidence: 99%
“…Poly vinyl chloride (PVC), as the most commonly used thermoplastic, is used in different kinds of fields in modern society [1][2][3]. There are two basic ways in which vinyl chloride monomer (VCM) can be widely produced: the hydrochlorination of acetylene and the oxychlorination of ethylene [2][3][4][5]. For acetylene hydrochlorination, Hg-based catalysts have been used as the main industrial catalysts for the production of VCM.…”
Section: Introductionmentioning
confidence: 99%
“…For acetylene hydrochlorination, Hg-based catalysts have been used as the main industrial catalysts for the production of VCM. However, mercuric component is volatile under the reaction conditions and thus do harmful to ecological environment and human beings [1][2][3][4][5][6]. Thus, replace of toxic Hg-based catalysts with non-mercury-containing alternatives would be significantly beneficial in this process [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…3 Later, Hutchings's group found that single-site cationic Au entities exhibited activity that correlated with the ratio of Au(I)/Au(III) in the catalyst. 4 Although the deactivation of the catalyst might be associated with the formation of metallic Au particles, 5 metallic Au played a role in the catalysis of acetylene hydrochlorination, when the size of Au nanoparticles was controlled to a very small scale. Perez-Ramirez et al found that Au single atoms hosted on N-doped carbon-derived by the controlled pyrolysis of polyaniline exhibited remarkable stability for acetylene hydrochlorination.…”
Section: Introductionmentioning
confidence: 99%